Impact of Three Bleaching Events on the Reef Resiliency of Kāne‘ohe Bay, Hawai‘i - Bahr, Keisha D.; Rodgers, Ku‘ulei S.; Jokiel, Paul L. (Frontiers in Marine Science, 2017)
Coral bleaching events have been increasing in frequency and severity worldwide. The most prolonged global bleaching event began in 2014 and continued into 2017 impacting more reefs than any previous occurrence. Here we present the results of coral bleaching and mortality surveys conducted in Kāneʻohe Bay Oʻahu, Hawaiʻi and compare them to the only other widespread bleaching events to impact the main Hawaiian Islands in 1996 and 2014. Results from these surveys along with associated environmental factors were used to compare these events to gain a baseline understanding of the physical processes that influence localized bleaching dynamics under these extreme environmental conditions. Survey results show extensive variation in bleaching (1996- 62%, 2014- 45%, 2015- 30%) and cumulative mortality (1996- <1%, 2014- 13%, 2015- 22%) between years. Bleaching prevalence was observed to decrease in certain reef areas across events, suggesting some acclimation and/or resilience, but possible increase susceptibility to mortality. Long-term monitoring sites show a similar temporal pattern of coral mortality and decline in coral cover, but revealed some reefs remained relatively un-impacted by consecutive high temperature events. Across the three bleaching events, we found that although circulation patterns can facilitate heating, the duration and magnitude of the high temperature event were found to be the primary forcing functions for coral bleaching and mortality. Other localized primary drivers influencing water temperature such as irradiance, turbidity, and precipitation contributed to spatial variations. Recovery and resilience of this coral reef ecosystem is dependent on many factors including duration and magnitude of heating, resulting mortality levels, localized environmental factors in the bay, and coral species affected and their bleaching tolerances.